(untitled) (Research, Society and Development, 2026)
Duchenne Muscular Dystrophy (DMD) is a rare, progressive genetic disorder associated with high morbidity and mortality, whose clinical management has evolved with advances in molecular diagnostics and disease-modifying therapies. However, in Brazil, significant gaps remain in scientific production, diagnostic access, and healthcare organization. This study aimed to analyze national scientific production on DMD, identifying methodological patterns, geographic distribution, diagnostic and therapeutic approaches, and knowledge gaps. This scoping review followed PRISMA-ScR guidelines. Searches were conducted in PubMed, SciELO, LILACS, and gray literature, considering publications from the last ten years. Original studies including Brazilian population data were selected. Study selection followed identification, screening, eligibility, and inclusion phases, and data were extracted and descriptively synthesized. Sixteen studies were included, with predominance of observational designs and case reports. Sample sizes ranged from 1 to 166 participants, with wide age variation. Cases were concentrated in the Southeast region (n = 154), followed by the Northeast (n = 94), South (n = 28), and North (n = 1), in addition to multicenter studies (n = 166). Studies addressed clinical, genetic, therapeutic, and economic aspects, highlighting the use of MLPA and NGS. Scientific production on DMD in Brazil is expanding but remains characterized by methodological heterogeneity and regional asymmetries, reinforcing the need for multicenter studies and early diagnosis strategies.